Pengaruh Konseling Kelompok dengan Pendekatan Cognitive Information Processing terhadap Peningkatan Kemampuan Pengambilan Keputusan Karir - Sadiqa Sadaf (Jurnal Psikologi, 2023)
This study aims to see whether there is an effect of group counseling with a cognitive information processing approach on improving career decision-making abilities in language major. The research method used in this study is an experimental research method with a one group pretest-posttest approach. The participants of this study are 28 people. The results show that career decision making before group counseling is carried out using cognitive information processing approaches shown by students is included in the low category, career decision making after conducting group counseling with a cognitive information processing approach that shown by students is included in the high category, with a difference of 0,68. In addition, the hypothesis results indicate that there is a significant difference between student career decision making before and after group counseling with a cognitive information processing approach. The results of this study are expected to be useful for BK teachers as well as career counsellors to help confused language majors in making their career decision.